Kireç-denizsuyu prosesi ile alg ayrımı - Üresin, Alpago (Fen Bilimleri Enstitüsü, 1996)
Natural waters, polluted either by man ör by nature, are likely to contain dissolved inorganic and organic substances, biological forms such as bacteria and plankton, and suspended inorganic material. To remove these substances, the usual unit processes include plain sedimentation, removal by coagulation generally to remove dissolved minerals like hardness components and iron and manganese. Other processes such as adsorption, aeration, ion exchange, oxidation, and distillation are also important for the removal of dissolved substances. Organic and inorganic constituents in domestic ör industrial wastewaters can be efficiently removed in a variety of ways. However, the materials removed during the treatment process are often left in a sludge which must be further treated before disposal. Numerous processes have been suggested for the removal of phosphates from wastewaters. Most of these methods are based on the addition of chemicals that convert the soluble phosphorus compounds into insoluble precipitates, a process that is follovved by the separation of the precipitate by gravity settling. Gravity settling is generally a slow process, and thus a comparatively large unit is required to provide for solids separation. it has already been pointed out that the settling velocities of finely divided and colloidal particles under gravity alone are so small that ordinary sedimentation is not practical. it is necessary, therefore, to use procedures which agglomerate the small particles into larger aggregates, which then have the settling velocities required to be practical. Flocculation and coagulation have been used indiscriminately in colloid chemistry to describe the aggregation process. in the technological context they are differentiated but the differentiation differs with the technology considered. Coagulation describes the effect produced by the addition of a chemical to a colloidal dispersion resulting in partide destabilization by a reduction of forces tending to keep the particles apart. Rapid mixing is important at this stage to obtain uniform dispersion of the chemical and the increase the opportunity for partide to partide contact. The second stage of formation of settleable particles from destabilized colloidal-sized partides is termed flocculation. in contrast to coagulation, where the primary force is electrostatic ör inter ionic, flocculation occurs by a chemical bridging ör physical enmeshment mechanism. Flocculation obtained by gentle and prolonged mixing vvhich converts the submicroscobic coagulated particles into discrete, visible, suspended particles. At this stage, the particles are large enough to settle rapidly under the influence of gravity. The use of lime in wastewater treatment systems will probably accelerate in the next few years. Lime is an effective precipitant for phosphates and many trace metals. Its use may result in excellent disinfection. in addition, lime act as a coagulant, dramatically increasing the degree to vvhich wastewater solids (colloids in particular) may be removed. Lime has several advantages över iron and aluminum (alum) salts, the other majör precipitating chemicals used in wastewater treatment. VVithin the range of doses required to produce effective phosphate removal, the chemical cost for lime treatment is lower. To date, the recovery of alum and iron reagents has not been exploited as successfully. in addition, ammonia, nitrogen may be stripped from the wastewater at the high pH produce by lime treatment, whereas this is not possible in the lower pH ranges where alum ör iron is used. There are many reasons why lime products are used worldwide. The main advantages are: - Lime is a natural product - is available everywhere - does not contain any toxic substances ör pollutants - is low-priced - is easy to handle - residues from lime-based processes can be easily stabilized. Precipitation of wastewater with lime has given variable results at different treatment plants. There may be a number of reasons for the variation in results found at locations. Many investigators have indicated that the magnesium concentration in the wastewater plays a very important role when using lime precipitation. Addition of magnesium as a coagulant may improve the phosphorus removal efficiency to a great extent. Because a higher magnesium content in the wastewater may lower the required döşe of lime and improve the effluent quality. Phosphorus occurs in natural water and spentwater streams almost exclusively as some of phosphate. Phosphate is the chemical term for the various combinations of phosphorus and the element oxygen. Of particular interest to spentwater treatment plant operation is water-soluble orthophosphate (the most highly hydrated form of phosphate, PO4 "3 ), whose presence is usually due to run-off of phosphate fertilizers and use of phosphate containing detergents. The discharge of phosphates into receiving vvaters is critical because, phosphorus has been implicated as a primary, and often limiting, algal nutrient; the removal of phosphorus from waste discharges is thought to be, in many instances, a feasible means of curtailing algal development. Phosphates are used widely in municipal and private water treatment systems and occur often in natural vvaters depending on the pH of the vvater and various kinds of soil formations the water has contacted. Phosphorus is often the nutrient limiting the summer phytoplankton grovvth, any reaction that removes the wastewater can be important for reduction of the algal grovvth. Algae are microscopic photosynthetic plants of simplest forms, having neither roots, stems, nor leaves. They range in size from tiny single cells, giving vvater a green color, to branched forms of visible length that often appear as attached green slime. There are hundreds of algal species in a wide variety of ceil structures in various shades of green and, less commonly brovvn and red. An alga is identified by microscopic observation of its essential characteristics. Algae are autotrophic, using carbon dioxide ör bicarbonates as a carbon source, and inorganic nutrients of phosphate and nitrogen as ammonia ör nitrate. in addition, certain trace nutrients are required, such as magnesium, boron, cobalt and calcium. The purpose of photosynthesis is to produce new plant life, thereby increasing the number of algae. Given a suitable environment and proper nutrients, algae grow and multiply in abundance. in natural vvaters the grovvth of algae may be limited by turbidity blocking sunlight, low temperatures during the vvinter, ör depletion of a key nutrient. The process of photosynthesis is illustrated by the equation : energy from sunlight CO2 + P04 + NH3 > new celi grovvth + O2 Algal carry-over in oxidation pond effluents can exert a significant oxygen demand in receiving vvaters. in recent years numerous processes for upgrading pond effluents vvere studied. Special emphasis vvas placed on the use of coagulating and flocculating materials to destabilize algal suspensions and effect removal by either settling ör flotation. Among the inorganic flocculants studied vvere lime and magnesium compounds. The main purpose of this study can be summarized in the follovving : 1. To find the optimal pH performance of lime-seawater combination. 2. To understand some of the mechanisms involved in chemical treatment with lime and seawater. 3. To investigate the effect of seavvater addition upon the suspended solids removal and phosphorus removal in conjunction with lime precipitation. 4. To determine the effectiveness of lime-seawater process for removing algae from effluents. Samples were collected from a drug plant. Influent includes domestic and some industrial wastewater. Table 1 shows mean characteristics of influent. TABLE 1. Mean Characteristics in the influent at Drug Plant. ~pH l 6.75 - 6.95 T?â l 68 mg/l Tot-P 3.29 mg/l "Mğ 69.9 mg/l COD (unfiltered) 500 mg O/l ~Pb 0.08 mg/l BODs(unfiltered) 140mgO/l NH4-N 10.1 mg/l Suspended Solids 200mg/l Zn 0.4 mg/l SO42 7.99 mg/l Specific Resistance 545 [jS/cm Seavvater represents an economical magnesium source for the experimental study. in contrast to the majör constituents in seavvater (Salinity = 35 %o) and the properties of seavvater used in the experiment are listed in Table 2 and Table 3. And also in Table 5, chemical and physical properties of hydrated lime used in the experiments are summarized. TABLE 2. The Majör Constituents in Seavvater ( Salinity = 35 %o). Cations mg/l Anions mg/l Natrium 10500 Chloride 19000 Potassium 380 Bromide 65 Magnesium 1350 Fluoride 1,3 Calcium 4ÖÖ Sulfate 265Î Strontium 8 Bicarbonate 141 TABLE 3. Properties of Seawater Used in the Experiments (Salinity = 18 %o - pH = 8.20 ). TABLE 4. Chemical and Physical Properties of Hydrated Lime Used in the Experiments In the experimental study standard jar test method was used. Lime doses were 0, 100, 300, 600, 1000, 1500, 2100, 2800, 3600 mg Ca(OH)2/l. Seven different test series were examined for pH performance and the amount of seawater was added in relation to total volume in jar in order to 0%, 1%, 2.5%, 5%, 10%, 20%, 30%. According to the pH performance the appropriate lime dosages were chosen. Furthermore, a flocculation procedure was carried out to determine total phosphorus, COD, BOD5, SS, TS, TDS, and ASH. Mixing time and intensity arranged in the flocculation procedure is shown ( Table 5 ). TABLE 5. Mixing Time and Intensity Arranged in the Flocculation Process All of total phosphorus measurements were done accurately by means of a UV spectrophotometer. The total phosphorus residual was achieved from 3.29 mg/l to approximately 0.49 mg/l and, 90% of suspended solids removal efficiency was obtained by decreasing suspended solids from 200 mg/l to 20 mg/l in the original wastewater. The results were favorable with seawater concentrations from 5 % to 20 % by volume and lime dosages from 600 to 1000 mg Ca(OH)2 / I. The lime-seawater process has considerable advantages for coastal communities. It may be a cost-effective for effluents if low-cost sources for lime and magnesium are available.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Algler; Deniz suyu; Kireç; Algae; Sea water; Lime